Survei Bibliografi Kajian Tafsir dan Fikih di Pondok Pesantren: Kajian Atas Materi Radikalisme dalam Literatur Pesantren dan Respon Kiai Terhadapnya - Ahmad Fawaid (Proceedings of Annual Conference for Muslim Scholars, 2018)
This paper attempts to figure out the bibliographical survey of Quranic exegesis (tafsīr) and Islamic jurisprudence (fiqh) in the three largest pesantren located at “Tapal Kuda” regencies of East Java, including Pesantren Zainul Hasan Genggong, Pesantren Nurul Jadid Paiton, and Pesantren Salafiyyah Syafi’iyah Sukerojo. This survey is based on an investigation of narratives on radicalism in these pesantren in terms of the Jalāl al-Dīn al-Maḥallī and Jalāl al-Dīn al-Suyūṭī’s exegesis work Tafsīr al-Jalālayn, and Abu Shujā’s jurisprudential work Fatḥ Al-Qarīb. By uing reception theory, this research is aimed to reveal the ways Moslem teachers (kiai or ustādh) of tafsīr and fiqh in these pesantren responded to the common stereotypical assumptions on ‘static, unchangeable, traditional’ pesantren, and the ways they provide reasonable conditions of the pesantren’s impunity in dealing with these stereotypes. The research of this study includes: (1) pesantren literatures on the basis of intellectual genealogical system; and (2) three strategies typically used by some kiais in reducing narratives on radicalism, such as historical, intertextual, and nationalism studies. In order to build a contra-narratives on radicalism, this research argues that Islamic jargon Raḥmatan li al-‘alamīn, especially in Tapal Kuda regencies, is partly interdependent on kiai’s cultural perceptions.